Cover image. (12th February 2021) - Tyler, Natasha; Giles, Sally; Daker‐White, Gavin; McManus, Beth Clare; Panagioti, Maria
Abstract : The cover image is based on the Original Research Paper A patient and public involvement workshop using visual art and priority setting to provide patients with a voice to describe quality and safety concerns: Vitamin B12 deficiency and pernicious anaemia by Natasha Tyler BSc (Hons), PhD et al., https://doi.org/10.1111/hex.13152 . Design Credit: Emma Barnard